Phenolic chalcones as agents against Trichomonas vaginalis - Oliveira, Lígia R [UNESP]; Trein, Márcia R; Assis, Letícia R [UNESP]; Rigo, Graziela V; Simões, Leonardo P M [UNESP]; Batista, Victor S [UNESP]; Macedo, Alexandre J; Trentin, Danielle S; Nascimento-Júnior, Nailton M [UNESP]; Tasca, Tiana; Regasini, Luis O [UNESP] (Elsevier, 2023)
Trichomonas vaginalis, a flagellated and anaerobic protozoan, is a causative agent of trichomoniasis. This disease is among the world's most common non-viral sexually transmitted infection. A single class drug, nitroimidazoles, is currently available for the trichomoniasis treatment. However, resistant isolates have been identified from unsuccessfully treated patients. Thus, there is a great challenge for a discovery of innovative anti-T. vaginalis agents. As part of our ongoing search for antiprotozoal chalcones, we designed and synthesized a series of 21 phenolic chalcones, which were evaluated against T. vaginalis trophozoites. Structure-activity relationship indicated hydroxyl group plays a role key in antiprotozoal activity. 4'-Hydroxychalcone (4HC) was the most active compound (IC50 = 27.5 µM) and selected for detailed bioassays. In vitro and in vivo evaluations demonstrated 4HC was not toxic against human erythrocytes and Galleria mellonella larvae. Trophozoites of T. vaginalis were treated with 4HC and did not present significant reactive oxygen species (ROS) accumulation. However, compound 4HC was able to increase ROS accumulation in neutrophils coincubated with T. vaginalis. qRT-PCR Experiments indicated that 4HC did not affect the expression of pyruvate:ferredoxin oxidoreductase (PFOR) and β-tubulin genes. In silico simulations, using purine nucleoside phosphorylase of T. vaginalis (TvPNP), corroborated 4HC as a promising ligand. Compound 4HC was able to establish interactions with residues D21, G20, M180, R28, R87 and T90 through hydrophobic interactions, π-donor hydrogen bond and hydrogen bonds. Altogether, these results open new avenues for phenolic chalcones to combat trichomoniasis, a parasitic neglected infection.